Cover Feature: Flavin‐Helicene Amphiphilic Hybrids: Synthesis, Characterization, and Preparation of Surface‐Supported Films (ChemPlusChem 7/2021). Issue 7 (14th June 2021) - Jakubec, Martin; Novák, David; Zatloukalová, Martina; Císařová, Ivana; Cibulka, Radek; Favereau, Ludovic; Crassous, Jeanne; Cytryniak, Adrianna; Bilewicz, Renata; Hrbáč, Jan; Storch, Jan; Žádný, Jaroslav; et al.
Abstract : The Cover Feature shows a newly prepared flavo[7]helicene 1 that combines inherent helical chirality with redox activity, which was studied in solution (both aqueous and organic phases), in layers (electropolymers), and in the solid state (a single crystal). In addition, a methodology that allows the loading of 1  enantiomers into an internally nanostructured lipid 1‐monoolein matrix was developed. More information can be found in the Full Paper by J. Vacek, J. Žádný and co‐workers .